TOKSISITAS LIMBAH CAIR LATEKS TERHADAP JUMLAH ERITROSIT, JUMLAH LEUKOSIT DAN KADAR GLUKOSA DARAH IKAN PATIN (Pangasius sp.) - Aris Susanto; Ferdinand Hukama Taqwa; Marsi . (Jurnal Akuakultur Rawa Indonesia, 2014)
ABSTRACT The purposes of this research were to determine the value of LC50 96 hours and sub lethal toxicity test of latex liquid waste against erythrocytes, leukocytes  and  blood glucose levels of catfish. This research was held from April until June 2013 in Laboratory of Basic Fisheries, Faculty of Agriculture, Sriwijaya University, Indralaya. The materials used for this research were latex liquid waste and bioassay used in this research are the catfish with length of 11 cm ± 0.1 cm with a weight of 10g ± 1g. Lethal toxicity test and sub lethal toxicity test used a Completely Randomized Design (CRD) with seven treatments and three replications. Treatment levels of lethal toxicity test were 0 mL.L-1(A), 16.8 mL.L-1 (B), 18.8 mL.L-1 (C), 21.0 mL.L-1 (D), 23.5 mL.L-1 (E), 26.3 mL.L-1 (F) and 29.4 mL.L-1(G). Treatment levels of sub lethal toxicity tests were 0% x LC50 96 hours (A), 0.5% x LC50 96 hours (B), 1% x LC50 96 hours (C), 6.25% x LC50 96 hours (D), 12.5% ​​x LC5096 hours (E), 25% x LC50 96 hours (F) and 50% x LC50 96 hours (G). The results of this research showed that the of LC50 96 hours concentration of latex liquid waste for catfish was 24.5 mL.L-1. Average value range of physical and chemical water properties during lethal toxicity tests were 28°C for temperature, pH between 6.6-6.9, dissolved oxygen between 1.98-2.96 mg.L-1 and ammonia between 0.056-0.402 mg.L-1. The results of sub lethal toxicity tests to control indicated that erythrocytes, leukocytes and blood glucose levels consecutive range 4.718-5.364 x 106 sel.mm-3, 388.97-447.87 x 103 sel.mm-3, 76.82-131.74 mg.dL-1. The results of sub lethal toxicity tests indicated that latex liquid waste concentrations affect the erythrocytes, leukocytes and blood glucose levels at concentrations above 6.25% x LC50 96 hours (1.5312 mL.L-1) with survival of catfish 96.67%. Average range value of physical and chemical water properties during sub lethal toxicity tests were 27.6 to 28°C for temperature, pH between 6.8 to 7.1, dissolved oxygen between 1.43 to 1.89 mg.L-1 and ammonia between 0.194 to 0.549 mg.L-1. Keywords: Latex liquid waste, toxicity, catfish, hematology